PENGEMBANGAN BUKU CERITA BERGAMBAR BILINGUAL PADA SISWA SEKOLAH DASAR - Regita Halid; Rusmin Husain; Fidyawati Monoarfa; Wiwy Triyanty Pulukadang; Sukri Katili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The formulation of the problem in this research is the initial learning conditions by using bilingual picture storybooks at SDN (State Elementary School) 2 Limboto Barat, how to develop bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat, and the feasibility of bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat. This research aims to describe the initial learning conditions using bilingual picture storybooks at SDN 2 Limboto Barat, develop bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat, and describe the feasibility of bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat. The method used is a development research method that uses the Thiagarajan (1974) model design, the 4D model, which consists of 4 stages: defining, designing, developing, and disseminating. The research findings demonstrated that the development of bilingual picture storybooks based on media expert validation obtained a percentage of 96% (very feasible), linguist validation obtained a percentage of 88% (very feasible), practitioner expert validation in terms of language and media obtained a percentage of 100% (very feasible). This validation obtained an average percentage of 96% (very feasible). Based on the findings, it can be concluded that the development of bilingual picture storybooks is very feasible to use in the learning process.